2016
DOI: 10.1021/acschembio.5b01069
|View full text |Cite
|
Sign up to set email alerts
|

Transition State Structure of RNA Depurination by Saporin L3

Abstract: Saporin L3 from the leaves of the common soapwort is a catalyst for hydrolytic depurination of adenine from RNA. Saporin L3 is a type 1 ribosome inactivating protein (RIP) composed only of a catalytic domain. Other RIPs have been used in immunotoxin cancer therapy, but off-target effects have limited their development. In the current study, we use transition state theory to understand the chemical mechanism and transition state structure of saporin L3. In favorable cases, transition state structures guide the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…2) [22] while the MEP of the catalytically inactive substrate analogue PD p A p GPD differs significantly, which is also consistent with the weaker binding of this compound ( K i * = 16.1 μM; Fig. 2 and Table 1).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…2) [22] while the MEP of the catalytically inactive substrate analogue PD p A p GPD differs significantly, which is also consistent with the weaker binding of this compound ( K i * = 16.1 μM; Fig. 2 and Table 1).…”
Section: Resultssupporting
confidence: 67%
“…Saporin L3 and saporin L3 A14C were expressed as excreted proteins in yeast cultures and purified to near-homogeneity as previously reported [5,22]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…154 The intrinsic primary 1′– 14 C KIE for saporin L3 depurination is 1.052, less than expected for a fully developed S N 2 mechanism, where the 1′– 14 C KIE value can be as large as 1.14. 175177 The smaller α-secondary hydrogen KIEs of 1.045 for saporin L3 compared to 1.163 for ricin A-chain also indicates a transition state with less dissociative character. Where does the bond order reside in the saporin L3 transition state?…”
Section: Ribosome-inactivating Proteinsmentioning
confidence: 99%
“…Structure‐function studies have identified five invariant active site residues conserved among wide range of RIPs and have shed light on their possible roles in the depurination of A 4324 /A 2660 . The current accepted N‐glycosidase mechanism involves aromatic stacking of the adenine to be cleaved between two invariant tyrosines, its protonation by an invariant arginine residue, stabilization of the resulting ribose oxocarbenium (ribocation) like transition state by adjacent invariant glutamate residue and nucleophilic attack by a catalytic water molecule at the C1′ position of ribose carbocation intermediate resulting in the cleavage of N9‐C1′ N‐glycosidic bond of susceptible adenosine.…”
Section: Introductionmentioning
confidence: 99%